Digital signal processing : - Tan, Li (Elsevier/Academic Press, 2013)
Bridging the gap between theory and application, this text covers all the main areas of modern DSP. Principles, applications, and hardware implementation issues are presented, and a wealth of worked examples and end of chapter exercises provide the opportunity for self-learning. Throughout the book emphasis is placed on applications to signal, image, and video processing, and real time implementation of DSP algorithms using DSP processors is highlighted.